Effect of cyanobacterial extract on in vitro propagation of Dendrobium anosmum Lindl. - Trương, Thị Bích Phượng; Tống, Văn Bảo Thạnh; Phan, Thị Thảo Nguyên; Nguyễn, Đức Tuấn; Lâm, Thị Ngọc Thuý; Hoàng, Thị Kim Hồng; Nguyễn, Thị Thu Liên (Hue University Journal of Science: Natural Science, 2022)
Protocorms of 4-week-old Dendrobium anosmum Lindl. were used as initial material for in vitro propagation. The stock extract of Arthrospira sp. was prepared by grinding 1 g of fresh biomass in 100 mL of distilled water. The in vitro propagation results show that the cyanobacterial extract has the effect of enhancing shoot multiplication and rooting of Dendrobium anosmum. An MS basal medium supplemented with 6 g·L–1 agar, 30 g·L–1 saccharose, and 1.5 mg·L–1 BAP in combination with 20 mL·L–1 cyanobacteria extract was suitable for protocorm multiplication with a protocorm cluster diameters of 2.43 cm. An MS medium supplemented with 6 g·L–1 agar, 30 g·L–1 sucrose, and 1.0 mg·L–1 BAP combined with 20 mL·L–1 cyanobacterial extract was optimal for shoot multiplication. The number of shoots/explant reached 4.7 and a shoot height of 1.37 cm. An MS medium supplemented with 6 g·L–1 agar, 30 g·L–1 sucrose, and 1.5 mg·L–1 NAA in combination with 30 mL·L–1 cyanobacteria extract was the most suitable for rooting with 4.87 roots/bud; the root length was 0.74 cm, and the shoot height was 2.76 cm. These results would open up the application of cyanobacterial extract to reduce costs in plant tissue culture technology.